Ammonia Dynamics in the Human Body: Insights in Biomedical Sensing Technologies - Annelot Nijkoops; Manuela Ciocca; Martina Aurora Costa Angeli; Silvia Pogliaghi; Soufiane Krik; Enrico Avancini; Niko Münzenrieder; Paolo Lugli; Luisa Petti (Advanced Sensor Research, 2025)
Abstract Advancements in sensor technologies capable of measuring key biomarkers can greatly enhance medical diagnostics and health monitoring, facilitating more effective diagnosis, treatment, and prevention. While there are numerous biomarkers of interest, gaseous ammonia (NH3) stands out due to its significance as an indicator of organ function (e.g., liver and kidney failure) or bacterial infections (e.g., Helicobacter pylori, Proteus mirabilis) in the body. This review discusses the metabolism and presence of NH3 in body organs, as well as clinical conditions associated with the regulation of NH3 concentrations. This paper reviews various sensing materials and parameters, along with current state‐of‐the‐art gas sensors capable of detecting NH3 for biomedical applications. Additionally, it addresses the challenges faced by biomedical sensing technologies already in use in medical applications. This review highlights that while NH3 sensing applications for breath analysis are already well‐developed, in vivo NH3 sensing remains in its early stages and faces significant challenges. Finally, promising future research directions for NH3 sensing are discussed, including the integration of NH3 sensors in catheters or in the Simulator of Human Intestinal Microbial Ecosystem, as well as the early detection of antibiotic‐resistant bacteria to enhance medical diagnostics.